Comprehensive index of extreme climate risk in China and urban sustainable development - Feng Dong; Siqing Wang; Guang Yang (Chinese Journal of Population, Resources and Environment)
Climate change severely challenges our ecosystem and society, affecting urban residents’ socioeconomic activities. Thus, assessing severe weather risk is crucial for evaluating urban sustainability; understanding trends, causes, and impacts on socioeconomic development; and supporting the United Nations Sustainable Development Goal (SDG) 13. Using meteorological data from 1980 to 2020, we investigate five disaster-causing severe weather events in China and construct a comprehensive index of extreme climate risk (CIECR) at the county, city, province, and national levels. The CIECR can identify high-risk regions and primary severe weather events and provide early warnings. We empirically test the impact of extreme climate risks on agricultural production, industrial structure, and labor employment. The results show high risks in Xinjiang, northern Inner Mongolia, and southern regions, with high temperatures, low temperatures, and high winds as the leading risks. At the national level, the extreme climate risk fluctuates, indicating climate warming. While risks reduce agricultural production and employment, they promote modern agriculture, industrial production, and urbanization. The novelty of the study lies in its development of the county-level CIECR, which can capture heterogeneity characteristics and provide microdata support for urban climate change research and efforts toward SDG 13. This study aids in mitigating climate risks; responding to climate change; and comprehensively analyzing the causes, trends, and impacts of extreme climate risks.